Konstruksi Jilbab sebagai Simbol Keislaman - Ahmadi, Dadi; Yohana, Nova (Mediator, 2007)
Veil usage is not only just a matter of fashion style. Moreover, veils symbolize many great values in Islamic tradition. No wonder if veil—or jilbab—are commonly found in many places, including campus, among students as well as lecturer. This research aimed to investigate the motivation of the girls in wearing jilbab. Using phenomenology approach to know more about subjectivity meanings constructed between research subjects, the research has finally revealed some motivations among the girls in wearing jilbab. There are three motives in wearing jilbab as found among Unisba’s students: theological motive, psychological motive, and fashionable motive. Such motive further implied on three different identities constructed by research subjects: Phenomenal Moslem Students, Fashionable Moslem Students, and Tolerant Moslem Students.